A TINY BROWN MONKEY ON THE BIG BLUE EARTH - Christie, Tory; Powell, Luciana Navarro (Mankato, Minnesota : Amicus Ink, 2019)
Illustrations and easy-to-read text show that a tiny monkey in South America is in a jungle that is in a country on a continent on the Earth.
Keywords: Perspective (Philosophy) -- Fiction; Monkeys -- Juvenile fiction